Azithromycin‐containing intermittent preventive treatment in pregnancy affects gestational weight gain, an important predictor of birthweight in Papua New Guinea – an exploratory analysis. Issue 4 (15th September 2015) - Unger, Holger W.; Wangnapi, Regina A.; Ome‐Kaius, Maria; Boeuf, Philippe; Karl, Stephan; Mueller, Ivo; Rogerson, Stephen J.
Abstract: In Papua New Guinea, intermittent preventive treatment with sulphadoxine‐pyrimethamine and azithromycin (SPAZ‐IPTp) increased birthweight despite limited impact on malaria and sexually transmitted infections. To explore possible nutrition‐related mechanisms, we evaluated associations between gestational weight gain (GWG), enrolment body mass index (BMI) and mid‐upper arm circumference (MUAC), and birthweight. We investigated whether the increase in birthweight associated with SPAZ‐IPTp may partly be driven by a treatment effect on GWG. The mean GWG rate was 393 g/week (SD 250; n  = 948). A 100 g/week increase in GWG was associated with a 14 g (95% CI 2.6, 25.4) increase in birthweight ( P  = 0.016). Enrolment BMI and MUAC also positively correlated with birthweight. SPAZ‐IPTp was associated with increased GWG [58 g/week (26, 900), P  < 0.001, n  = 948] and with increased birthweight [48 g, 95% CI (8, 880), P  = 0.019] when all eligible women were considered ( n  = 1947). Inclusion of GWG reduced the birthweight coefficient associated with SPAZ‐IPTp by 18% from 44 to 36 g ( n  = 948), although SPAZ‐IPTp was not significantly associated with birthweight among women for whom GWG data were available ( P  = 0.13, n  = 948). One month post‐partum, fewer women who had received SPAZ‐IPTp had a low post‐partum BMI (<18.5 kg m −2 ) [adjusted risk ratio: 0.55 (95% CI 0.36, 0.82), P  = 0.004] and their babies had a reduced risk of wasting [risk ratio 0.39 (95% CI 0.21, 0.72), P  = 0.003]. SPAZ‐IPTp increased GWG, which could explain its impact on birthweight and maternal post‐partum BMI. Future trials of SPAZ‐IPTp must incorporate detailed anthropometric evaluations to investigate mechanisms of effects on maternal and child health.